Pengaruh Soft Skill Dan Hard Skill Terhadap Kesiapan Kerja (Studi Komparasi Gen Z Dan Gen M) Di Kota Bengkulu - Raihan, Muhamad; Nengsih, Mimi Kurnia (Jurnal Fokus Manajemen, 2024)
This study aims to find out the impact of soft skills and hard skills on employment readiness (comparative study of Gen Z and Gen M) in Bengkulu City. This type of research is a type of quantitative descriptive research, the object of this a research is Gen Z and Gen M in Bengkulu City. The population in this study is unknown because of the large number and scope of objects so wide that the method used is non-probability sampling. The method used for determining the sample is random Sampling which determines the number of samples used in this research using the Cochran formula with 91 Gen Z samples and 91 Gen M samples. The data collection method uses a questionnaire using an ordinal scale measurement tool. Data analysis techniques using Dual Liniear Regression Analysis Test, Hypothesis Test and Paired t – test .The results of this research can be concluded that the variables Soft Skill and Hard Skill have a positive and significant influence on Work Preparedness.